Celestin kot slovensko-hrvatski popularizator Turgenjeva - Barbarič, Štefan (Slavistična revija, 1977)
For a quarter of a century (since 1869) Fran J. Celestin was active in informing the Slovenes about the literature of Turgenev. In a number of articles dealing with various issues he was calling special attention to those constituent elements of the work of the Russian novelist which he could bring into focus in his own programing of the realist concept. The article outlines Celestin's activity in this line and offers an evaluation of it.
Keywords: Celestin, Fran; literarni stiki; ruska književnost; slovensko ruski stiki; Turgenev, Ivan Sergeevič